A tandem Kunitz protease inhibitor (KPI106)–serine carboxypeptidase (SCP1) controls mycorrhiza establishment and arbuscule development in Medicago truncatula. (13th June 2013) - Rech, Stefanie S.; Heidt, Sven; Requena, Natalia
Summary Plant proteases and protease inhibitors are involved in plant developmental processes including those involving interactions with microbes. Here we show that a tandem between a Kunitz protease inhibitor (KPI106) and a serine carboxypeptidase (SCP1) controls arbuscular mycorrhiza development in the root cortex of Medicago truncatula. Both proteins are only induced during mycorrhiza formation and belong to large families whose members are also mycorrhiza‐specific. Furthermore, the interaction between KPI106 and SCP1 analysed using the yeast two‐hybrid system is specific, indicating that each family member might have a defined counterpart. In silico docking analysis predicted a putative P1 residue in KPI106 (Lys173) that fits into the catalytic pocket of SCP1, suggesting that KPI106 might inhibit the enzyme activity by mimicking the protease substrate. In vitro mutagenesis of the Lys173 showed that this residue is important in determining the strength and specificity of the interaction. The RNA interference (RNAi) inactivation of the serine carboxypeptidase SCP1 produces aberrant mycorrhizal development with an increased number of septated hyphae and degenerate arbuscules, a phenotype also observed when overexpressing KPI106. Protease and inhibitor are both secreted as observed when expressed in Nicotiana benthamiana epidermal cells. Taken together we envisage a model in which the protease SCP1 is secreted in the apoplast where it produces a peptide signal critical for proper fungal development within the root. KPI106 also at the apoplast would modulate the spatial and/or temporal activity of SCP1 by competing with the protease substrate.